THE INFLUENCE OF LEADERSHIP, ORGANISATIONAL CULTURE, AND TECHNOLOGY ON THE EFFECTIVENESS OF HEALTHCARE MANAGEMENT: A LITERATURE REVIEW OF OPERATIONAL STANDARDS, SERVICE INNOVATION, AND RISK MANAGEMENT IN HOSPITALS - Andreas Harry; Gunawan Widjaja (Adisam Publisher, 2025)
This study aims to analyse the influence of leadership, organisational culture, and technology on the effectiveness of healthcare management through a literature review approach that focuses on operational standards, service innovation, and risk management in hospitals. This study is motivated by the increasing demands for quality, safety, and efficiency in healthcare services in the era of digital transformation. Data was collected through analysis of relevant scientific literature, including nationally and internationally indexed journals, scientific books, and health policy reports. The results of the study show that leadership plays a role in determining the strategic direction and stability of the organisation, organisational culture shapes the values and work behaviours that support system effectiveness, while technology enhances speed, accuracy, and innovation in service management. The synergy of these three factors has been proven to create more adaptive, effective, and sustainable healthcare management. The application of visionary leadership, a collaborative work culture, and the comprehensive integration of health information technology are key to facing global dynamics and increasing the competitiveness of hospitals in Indonesia